KAJIAN ASPEK LEGAL PENGENAAN PPH FINAL PENGALIHAN HAK ATAS TANAH DAN BANGUNAN DAN BPHTB TERHADAP TRANSAKSI LEASING TANAH DAN BANGUNAN - WASHINGTON WASHINGTON (PREMISE LAW JURNAL, 2015)
Leasing transaction related to the obligation to pay off Final PPh of land and building transfer and BPHTB was interested to be analyzed with the title. The conclusion of the research was that Final PPh assessment of land and building transfer and BPHTB for those who were involved in land and building leasing transaction if it is related to Final PPh assessment of land and building transfer in contract by the time the lessee used his option right and lessee back, the lessor would one 5% (five percent) in residual value, while in sale, the lessor would pay off the income tax 5% (five percent) of the highest value with NJOP of land and building. On the other hand, the levy on BPHTB, the transfer of land and building rights, in the leasing transaction of land and building is not regulated clearly by Law No. 28/2009 on State and Local Tax and Retribution. The role of a Notary/PPAT (official empowered to draw up land deeds) in levying PPh and BPHTB in leasing transaction of land and building transfer is by requesting a regulation which can accelerate the validation of registration process in land right transfer. A Notary /PPAT also has the obligation to appeal to tax payers to pay off their tax above NJPO so that the validation process can run smoothly, and there will be no obstacle in the validation process in Dispenda (Regional Revenue Agency). The obstacle form the legal aspect in levying Final PPh and BPHTB on leasing transaction in land and building transfer is that there is no synchronization of regulation between levying Final PPh in Law implementation and levying BPHTB in Law No. 28/2009 on government and local taxes and regional retribution. Keyword: Final PPh in Land and Building Transfer, BPHTB, Leasing of Land and Building, Legal Aspect